Corporatisation and accounting change: the role of accounting and accountants in a Malaysian public utility - Abu Kasim, Nor Aziah; Scapens, Robert W. (Elsevier, 2007)
Using an explanatory case study, this paper presents an in-depth analysis of a Malaysian public utility which was required to transform itself into a self-financing, efficient and profitable organisation through a process of corporatisation. Despite attempts to enhance profitability by imposing new rules of budgeting, and by recruiting new accounting graduates, the case reveals that although accounting changes were enacted, over time they became separated from, and only loosely coupled to, other organisational activities. Concepts from institutional theory were used as sensitising devices to inform the research, but alone they were unable to fully explain the case. Consequently, an extended framework, which treats loose coupling as both a process and an outcome, and which recognises the intertwining of trust, resistance and power was developed. This theoretical framework provides a possible explanation for the mixed findings about the effectiveness of public sector financial reform which have been revealed in a wide array of research studies.